# How do you solve this problem

S=2brh+2br(squared) solve for h

## To simplify

S= 2brh + 2br^{2}

take out the multiple common

S= 2br(h+2br)

S/2br= h+ 2br

(S/2br)-2br= h

## Um I forgot to go and

put a bracket around the 2br to give

**(2br) ^{2} since the answer would be different if that was the case but I'm assuming that the one I type now is what it was.**

## To solve for `h` in the equation S = 2brh + 2br², you can follow these steps:

Step 1: Start by isolating the term that contains `h` on one side of the equation. In this case, we want to get rid of the other terms first. Subtract 2br² from both sides of the equation:

S - 2br² = 2brh

Step 2: Now, we need to isolate `h`. Divide both sides of the equation by 2br:

(S - 2br²) / (2br) = h

Step 3: Simplify the equation on the right side:

h = (S - 2br²) / (2br)

That's it! You have solved for `h` in terms of the given equation S = 2brh + 2br².